2015
DOI: 10.1111/jocn.12816
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative psychological distress, coping and quality of life in Chinese patients with newly diagnosed gastric cancer

Abstract: Nursing professionals need to carefully assess the psychological status of patients with gastric cancer. Tailored interventions can be administered to help these patients appropriately cope with the disease and to enhance their quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
39
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 31 publications
4
39
3
Order By: Relevance
“…15,20 In fact, gastric cancer patients with emotional distress report using negative coping strategies (eg, avoidance, suppression, resignation) and have a poor quality of life. 21 Intrapersonal EC predicted the patients' adjustment more strongly than interpersonal EC, as shown previously. In fact, intrapersonal EC seems to have a greater effect on personal issues such as healthrelated variables in clinical and general populations.…”
Section: Discussion-conclusionsupporting
confidence: 80%
See 2 more Smart Citations
“…15,20 In fact, gastric cancer patients with emotional distress report using negative coping strategies (eg, avoidance, suppression, resignation) and have a poor quality of life. 21 Intrapersonal EC predicted the patients' adjustment more strongly than interpersonal EC, as shown previously. In fact, intrapersonal EC seems to have a greater effect on personal issues such as healthrelated variables in clinical and general populations.…”
Section: Discussion-conclusionsupporting
confidence: 80%
“…EC also enables better health behaviors and social support . In fact, gastric cancer patients with emotional distress report using negative coping strategies (eg, avoidance, suppression, resignation) and have a poor quality of life …”
Section: Discussion‐conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…In China, there were approximately 679,100 new cases and 498,000 deaths of stomach cancer in 2015, ranking second after lung cancer among all cancer types [2]. Hong et al reported that the prevalence of clinically signi cant preoperative psychological distress was 76.97% in Chinese patients with newly diagnosed stomach cancer 3 . In addition, patients with clinically psychological distress were more likely to have poor quality of life and to demonstrate negative coping styles [3].…”
Section: Introductionmentioning
confidence: 99%
“…Hong et al reported that the prevalence of clinically signi cant preoperative psychological distress was 76.97% in Chinese patients with newly diagnosed stomach cancer 3 . In addition, patients with clinically psychological distress were more likely to have poor quality of life and to demonstrate negative coping styles [3]. In the research site, the research team found that most stomach cancer patients have a low education level and a high age [4].…”
Section: Introductionmentioning
confidence: 99%